Liposomal Formulation to Increase Stability and Prolong Antineuropathic Activity of Verbascoside - Isacchi, Benedetta; Bergonzi, Maria Camilla; Iacopi, Romina; Ghelardini, Carla; Galeotti, Nicoletta; Bilia, Anna Rita (Planta Medica, 2017)
Verbascoside (acteoside) possesses various pharmacological properties for human health, including antioxidant, anti-inflammatory, and antineoplastic properties in addition to numerous wound healing and neuroprotective properties, with an excellent and well-known safety profile. However, its poor chemical stability, due to hydrolysis, limits its use in the clinic. To overcome these limitations, we prepared unilamellar liposomal formulations of verbascoside for parenteral administration.Two formulations were prepared: V-L1 and V-L2, where V-L2 contains phospholipid and cholesterol about 4 times higher than the V-L1 sample, and about 2 times higher than verbascoside. The mean particle size of the liposomes prepared was found to be around 120 nm with a polydispersity index < 0.2. Encapsulation efficacy resulted in 30 %. A total of 82.28 ± 1.79 % of verbascoside was released from the liposomes within 24 hours. Liposomes ameliorate the stability of verbascoside by preventing its hydrolysis.The optimized drug delivery formulation was tested in the paw pressure test in two animal models of neuropathic pain: a peripheral mononeuropathy was produced either by a chronic constriction injury of the sciatic nerve or by an intra-articular injection of sodium monoiodoacetate. The performance of the liposomal formulation was compared with that of the free drug.For evaluating the paw pressure test in chronic constriction injury rats, a liposomal formulation administered i. p. at the dosage of 100 mg/kg showed a longer lasting antihyperalgesic effect in comparison with a 100-mg/kg verbascoside saline solution, as well as in the sodium monoiodoacetate models. The effect appeared 15 min after administration and persisted for up to 60 min.
Keywords: verbascoside-loaded unilamellar liposomes; prolonged activity; prolonged release; antineurophatic activity; in vivo study